2007
DOI: 10.1111/j.1365-2990.2007.00829.x
|View full text |Cite
|
Sign up to set email alerts
|

Relevance of combinatorial profiles of intermediate filaments and transcription factors for glioma histogenesis

Abstract: In order to define specific markers for histogenesis of three well-characterized subgroups of human gliomas (pilocytic astrocytomas, glioblastoma multiforme and oligodendrogliomas), we studied the expression of relevant markers that characterize gliomagenesis, by immunohistochemistry and in situ hybridization. They include the intermediate filament proteins glial fibrillary acidic protein (GFAP), vimentin and nestin, the transcription factors Olig2, Nkx2.2 and Sox10, and the proteolipid protein transcripts plp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
26
0
2

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 45 publications
3
26
0
2
Order By: Relevance
“…Consistently with several other studies we have reported that Sox10 is expressed in both paediatric and adult gliomas and ependymomas with a higher expression in low grade tumours compared to high grade tumours (Addo-Yobo, et al, 2006;Bannykh, et al, 2006;Colin, et al, 2007;Ferletta, et al, 2007). On the contrary Schlierf et al found that when investigating the mRNA levels of Sox10 in glioma the expression levels were lower compared to adult brain (Schlierf, et al, 2007).…”
supporting
confidence: 71%
See 2 more Smart Citations
“…Consistently with several other studies we have reported that Sox10 is expressed in both paediatric and adult gliomas and ependymomas with a higher expression in low grade tumours compared to high grade tumours (Addo-Yobo, et al, 2006;Bannykh, et al, 2006;Colin, et al, 2007;Ferletta, et al, 2007). On the contrary Schlierf et al found that when investigating the mRNA levels of Sox10 in glioma the expression levels were lower compared to adult brain (Schlierf, et al, 2007).…”
supporting
confidence: 71%
“…Some researchers have tried to subgroup well-characterized gliomas depending on their expression of GFAP, vimentin, Olig2, Nkx2.2, Sox10 and nestin. They suggest that gliomas with strong expression of GFAP, vimentin, Olig2, Nkx2.2 and Sox10 can be identified as pilocytic astrocytomas, further robust expression of GFAP, vimentin and nestin can categorize GBM and oligodendrogliomas can be recognized by Olig2 expression in almost all tumour cells while Sox10 and Nkx2.2 was found in subpopulations of tumour cells, these findings are not definite but may to some degree extend the diagnostic possibilities (Colin, et al, 2007). Moreover the study indicate how heterogeneous the gliomas are and emphasize the difficulties in finding treatment that will target all different tumour cells from the bulk cells to the tumor-initiating cells.…”
mentioning
confidence: 96%
See 1 more Smart Citation
“…Nestin is classified as a type VI intermediate filament protein [1]. During neural embryogenesis, nestin is expressed in neuroepithelial stem cells and is then downregulated in most mature central nervous system (CNS) cells [1].…”
Section: Introductionmentioning
confidence: 99%
“…To visualize human tumor cells in the rat brain and to determine their distribution outside the tumor core, we used a human-specific nestin staining, a protein expressed by the vast majority of GBM cells (15,22,23). Interestingly, treated tumors revealed a more homogeneous morphology compared with the controls (Fig.…”
Section: Anti-vegf Treatment Reduces Vessel Density and Strongly Incrmentioning
confidence: 99%